2014
DOI: 10.1179/2045772313y.0000000181
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac arrhythmias the first month after acute traumatic spinal cord injury

Abstract: Objective: Cardiovascular complications including cardiac arrest and arrhythmias remain a clinical challenge in the management of acute traumatic spinal cord injury (SCI). Still, there is a lack of knowledge regarding the characteristics of arrhythmias in patients with acute traumatic SCI. The aim of this prospective observational study was to investigate the occurrence of cardiac arrhythmias and cardiac arrests in patients with acute traumatic SCI. Methods: As early as possible after SCI 24-hour Holter monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…8,14,15 Bunten et al 13 reported that tetraplegics are more susceptible to low frequency and impaired variability of heart rate when compared with paraplegics and able-bodied individuals. Using both 24-h Holter monitoring and 12-lead ECG, Bartholdy et al 5 documented that patients with cervical SCI had significantly lower heart rates within the first month post injury when compared with patients with thoracic SCI. Their results also suggested that patients with cervical SCI are more susceptible to bradycardia, sinus node arrest, supraventricular tachycardia and, more rarely, cardiac arrest during the first month after cervical SCI, whereas only a few patients with thoracic SCI developed sinus node arrests and bradycardia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…8,14,15 Bunten et al 13 reported that tetraplegics are more susceptible to low frequency and impaired variability of heart rate when compared with paraplegics and able-bodied individuals. Using both 24-h Holter monitoring and 12-lead ECG, Bartholdy et al 5 documented that patients with cervical SCI had significantly lower heart rates within the first month post injury when compared with patients with thoracic SCI. Their results also suggested that patients with cervical SCI are more susceptible to bradycardia, sinus node arrest, supraventricular tachycardia and, more rarely, cardiac arrest during the first month after cervical SCI, whereas only a few patients with thoracic SCI developed sinus node arrests and bradycardia.…”
Section: Discussionmentioning
confidence: 99%
“…Their results also suggested that patients with cervical SCI are more susceptible to bradycardia, sinus node arrest, supraventricular tachycardia and, more rarely, cardiac arrest during the first month after cervical SCI, whereas only a few patients with thoracic SCI developed sinus node arrests and bradycardia. 5 The present study is an original examination of several electrocardiographic parameters during the initial 72 h post trauma among patients grouped according to their level and severity of spine trauma. Overall, this study shows that patients with motor complete SCI at cervical or high-thoracic level had significantly longer RR interval, shorter QTc interval and more prolonged duration of the longest QRS complex than patients with less severe spine trauma caudal to the T6 level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results could be related to injury in the sympathetic innervation of the heart more that the unopposed parasympathetic activity thus helping to increase risk of atrioventricular blocks, ventricular arrhythmias and cardiac sudden death. 27 However, most studies measured the QT interval mainly during in the acute phase of the SCI, mainly after first month. 14,26,27 On the other hand, subjects with cervical SCI and practitioners of physical exercise showed reduction of the myocardial atrophy due changes in the pressure and volume imposed to the heart exercise-induced.…”
mentioning
confidence: 99%